Opportunity and performance : equity for children from poverty - Cavazos, Linda; Layland, Allison; Twyman, Janet; Vuong, Bi (Emerald Publishing Limited, 2021)
Because everyone from policymakers to classroom teachers has a role in achieving greater equity for children from poverty, this book provides a sweeping chronicle of the historical turning points--judicial, legislative, and regulatory--on the road to greater equity, as background to the situation today. It provides succinct policy recommendations for states and districts, as well as practical curricular and instructional strategies for districts, schools, and teachers. This comprehensive approach--from the statehouse to the classroom--for providing children who come to school from impoverished environments with the education in which they thrive, not merely one that is comparable to others, truly enlists everyone in the quest for opportunity and performance. The next step toward equity may be taken by a governor, but it may also be taken by a teacher. One need not wait for the other.
Includes index.
Keywords: Poor -- Political aspects.; Education -- Educational Policy & Reform -- General.; Educational strategies and policy.; elektronické knihy; electronic books